Density biases and temperature relations for DESIRED H ii regions - Méndez-Delgado, José Eduardo; Esteban, C; García-Rojas, J; Arellano-Córdova, K Z; Kreckel, Kathryn; Gómez-Llanos, V; Egorov, Oleg; Peimbert, M; Orte-García, M (Monthly notices of the Royal Astronomical Society, 2023)
We present a first study based on the analysis of the DEep Spectra of Ionized REgions Data base (DESIRED). This is a compilation of 190 high signal-to-noise ratio optical spectra of HII regions and other photoionized nebulae, mostly observed with 8–10 m telescopes and containing ∼29 380 emission lines. We find that the electron density –ne– of the objects is underestimated when [SII] λ6731/λ6716 and/or [OII] λ3726/λ3729 are the only density indicators available. This is produced by the non-linear density dependence of the indicators in the presence of density inhomogeneities. The average underestimate is ∼300 cm−3 in extragalactic HII regions, introducing systematic overestimates of Te([OII]) and Te([SII]) compared to Te([NII]). The high-sensitivity of [OII] λλ7319 + 20 + 30 + 31/λλ3726 + 29 and [SII] λλ4069 + 76/λλ6716 + 31 to density makes them more suitable for the diagnosis of the presence of high-density clumps. If Te([NII]) is adopted, the density underestimate has a small impact in the ionic abundances derived from optical spectra, being limited to up to ∼0.1 dex when auroral [SII] and/or [OII] lines are used. However, these density effects are critical for the analysis of infrared fine structure lines, such as those observed by the JWST in local star forming regions, implying strong underestimates of the ionic abundances. We present temperature relations between Te([OIII]), Te([ArIII]), Te([SIII]), and Te([NII]) for the extragalactic HII regions. We confirm a non-linear dependence between Te([OIII]) and Te([NII]) due to a more rapid increase of Te([OIII]) at lower metallicities.